Treatment of brain diseases: therapeutic strategies to overcome the blood-brain barrier - Vicente, Sara Sousa da Cruz (2023)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2023, Universidade de Lisboa, Faculdade de Farmácia.